ANALISIS KEUNGGULAN BERSAING BERDASARKAN MATRIKS BCG (BOSTON CONSULTING GROUP) PADA PERUMDA AIR MINUM WAY RILAU KOTA BANDAR LAMPUNG) - Lindah Widyastuti; K. Bagus Wardianto (Jurnal Kompetitif Bisnis, 2023)
A company that is founded generally aims to obtain large profits, one way is to increase the volume of sales made by the company as its main goal, the strategy really needs to be used to develop and improve the company's business. The data collection method used is field research methods such as observation, interviews and documentation. This type of research is descriptive research. The approach in this research is qualitative and quantitative, because descriptive data in the form of writing and research data in the form of numbers. Sources of data used are primary data, data obtained directly from direct observations in the field and also conducting interviews with the company to obtain data and secondary data can be obtained from data that has been processed. The results of the BCG matrix analysis show that the Market Growth Rate (TPP) of PERUMDA Air Minum Way Rilau in Bandar Lampung City is 8% and the Relative Market Share (PPR) is 2.92x where the market share value is greater than 1 (> 1) so it is in the cash cows quadrant, which means an analysis of the low market growth rate and high market share. The strategy that can be used is the harvest strategy, which aims to reduce investment. To maximize market profits and maintain market share that has been controlled by focusing on the target market so that in the future it can reach areas that are currently still unreached, improve the quality of customer service and increase product promotion online through social media in increasing profits.